The clinical application of ear keloid using five-blade core excision combined with pressure and superficial electron beam radiation - Qi, Ying; Xu, Suling; Wang, Jieyi; Xin, Chao; Li, Xiaohui; Lin, Bingjiang (Frontiers in Medicine, 2025)
BackgroundSurgical removal is the primary method for the clinical treatment of ear keloids. However, there are numerous surgical options available, and no standardized approach in the literature.ObjectivesThis study aimed to evaluate the impact of five-blade core excision on the removal of ear keloids.MethodsA preliminary study involving 11 patients (21 lesions) with ear keloids was conducted between January 2023 and December 2023. Five-blade core excision was performed; superficial electron beam radiotherapy was administered at a dose of 4 Gy for 5 post-operative consecutive days, and pressure clips were applied for 6 months. The Vancouver Scar Scale (VSS) and the Patient and Observer Scar Assessments Scale (POSAS) were used to assess the results.ResultsThe mean age of the patients was 24.36 years (18–44 years). Postoperative follow-up ranged from 20 months. The patients underwent 5 days of postoperative radiotherapy and pressure clips for 6 months. Nine patients had no recurrence, whereas two patients had a mild recurrence (one patient rejected radiotherapy). The VSS and POSAS scores significantly decreased (p < 0.01).ConclusionFive-blade core excision combined with pressure and superficial electron beam radiotherapy demonstrates effective therapeutic outcomes for ear keloid.